Hyperglobulinaemia in the portacaval shunted rat : an experimental study. - Keraan, Mogamat Mustapha (University of Cape Town, 2015)
The construction of a portacaval shunt in the rat is followed by a series of characteristic phenomena : weight loss, hypo-albuminaemia, hyperglobulinaemia and an increase in the circulating antibacterial antibody levels to endogenous bowel micro-organisms. The weight loss is characterised by several weeks of decreasing weight followed by a slow progressive reversal to normality and it has its origins in postoperative anorexia. The hypo-albuminaemia to some extent parallels the weight loss but never reaches the same magnitude and it too is likely to be closely associated with anorexia. The hyperglobulinaemia which is polyclonal embraces a rise in all three major immunoglobulin classes of the rat. Evidence is presented that links this polyclonal hyperglobulinaemia to enhanced antibacterial antibodies which increase following the portacaval shunt. The shunt is believed to effectively separate the reticulo-endothelial system of the liver from the portal circulation thus allowing unlimited and constant access of antigenic material from the bowel to immunocompetent cells. Evidence is also advanced that such material from microorganisms may also stimulate other immune reactions. Similar studies in the pig are also presented and the close parallel with chronic human liver disease led to the development of an hypothesis that portal shunting of blood is the cause of hyperglobulinaemia in man. The rat is suggested as a suitable model for the experimental reproduction of human hyperglobulinaemia.